Amino Amide Organocatalysts for Asymmetric Michael Addition of β-Keto Esters with β-Nitroolefins - Owolabi, Isiaka Alade; Chennapuram, Madhu; Seki, Chigusa; Okuyama, Yuko; Kwon, Eunsang; Uwai, Koji; Tokiwa, Michio; Takeshita, Mitsuhiro; Nakano, Hiroto (Bulletin of the Chemical Society of Japan, 2019)
Asymmetric Michael addition of β-keto esters with trans-β-nitroolefins using chiral amino amide organocatalyst was tried and afforded synthetically useful chiral Michael adducts in both excellent chemical yields (up to 99%) and stereoselectivities (up to dr. 99:1, up to 98% ee).